Solusi Pencegahan Korupsi dalam Al-Qur’an - Budi Suhartawan (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
Corruption has become a structural, cultural and personal problem. It iseven categorized as a major crime that has created dangerous problems and threatsbecause it can damage the stability and security of the state and also the moraldecline of the people. This research aims to uncover and analyze how corruption isseen in the Qur'an, understand what types of corruption are, what are the mainfactors of corrupt behaviour and what and how the Qur'an offers solutions regardingcorruption prevention. The method used in this study is a thematic-based librarymethod that focuses on reviewing the literature related to the discussion theme. Theresults of this study are that the Qur'an provides solutions to prevent corruption by:first, building civil society, second, improving oneself through identityidentification, third, building Good Governance (good governance), and actualizingvalues. tazkiyatun nafs.